Reproducibility of fetal lung‐to‐head ratio in left diaphragmatic hernia across the North American Fetal Therapy Network (NAFTNet). (29th January 2019) - Abbasi, Nimrah; Ryan, Greg; Johnson, Anthony; Sanz Cortes, Magda; Sangi‐Haghpeykar, Haleh; Ye, Xiang Y.; Shah, Prakesh S.; Benachi, Alexandra; Saada, Julien; Ruano, Rodrigo; ,
Abstract: Objective: To determine the antenatal sonographic lung area measurement method in left congenital diaphragmatic hernia (CDH) with the highest interrater agreement among North American Fetal Therapy Network (NAFTNet) centers within and outside the fetoscopic tracheal occlusion (FETO) consortium and in comparison with a European "expert" reviewer (ER). Methods: Nineteen members from nine FETO consortium centers and 29 reviewers from 17 non‐FETO centers reviewed ultrasound clips of the chest from 13 fetuses with isolated left CDH and were asked to select a static plane for lung area measurement using anteroposterior (AP), longest, and trace methods. Interrater agreement in lung area measurements was determined using intraclass correlation coefficient (ICC). Bland‐Altman analysis was used to evaluate mean difference (bias) between NAFTNet reviewers and ER. Results: Among FETO centers, agreement was highest using trace (ICC 0.94; 95% CI, 0.83‐0.98), followed by longest (ICC 0.89; 95% CI, 0.75‐0.97) and lowest for A‐P (ICC 0.83; 95% CI, 0.67‐0.94). Similar trends were noted in non‐FETO centers. When compared with ER, bias was lowest for trace: 14 ± 38 mm 2 and 19 ± 36 mm 2 for FETO and non‐FETO centers, respectively. Conclusion: The trace method demonstrated the highest interrater agreement and lowest bias for lung area estimation in left CDH across NAFTNet. Abstract : What is already known about this topic? As pulmonary hypoplasia is a major contributor to neonatal morbidity and mortality in congenital diaphragmatic hernia (CDH), antenatal prognostication relies heavily on sonographic fetal lung volume estimation by obtaining the observed to expected lung‐to‐head ratio (o/e LHR). Although prenatal counselling is based primarily on o/e LHR, significant inter‐rater variability has been reported, mostly related to the use of different lung area measurement methods (ie antero‐posterior, longest and trace). What does this study add? When comparing lung area measurement methods on de‐identified sonographic clips of left CDH across 26 centers within the North American Fetal Therapy Network and in comparison with an external European reviewer, the trace method demonstrated the highest inter‐rater agreement with the lowest bias. Standardization of antenatal CDH prognostication should begin with the adoption of the trace method for lung area estimation in CDH across fetal medicine sites.